Electromagnetic Nondestructive Testing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint focuses on the latest electromagnetic nondestructive testing technology and its applications, including magnetic flux leakage testing, eddy current testing, remote field eddy current testing, pulsed eddy currents, magnetic Barkhausen noise testing, electromagnetic acoustic transducer testing, etc. With the development of electromagnetic nondestructive testing, defect quantification and 3D imaging have become possible. The subject of detection has been extended from macroscopic defects to microscopic stresses, covering the whole course of a failure. Special attention is given to the fusion of multiple methods, new feature extraction methods, and new signal processing methods with artificial intelligence.